Teachers' Perceptions Of The Implementation Of English Language Learning In The Merdeka Curriculum - Inayah Syah Putri Telaumbanua (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The introduction of the Independent Curriculum in Indonesia brought significant changes to English language learning. This study investigates English teachers' perceptions of the implementation of this curriculum, exploring their experiences, challenges and opportunities within the new framework. Through descriptive research methods, we seek to understand how teachers adapt to a focus on student-centered learning. Our findings will contribute to a deeper understanding of the ongoing implementation process and provide valuable insights to support teachers and optimize English learning outcomes in the Merdeka Curriculum.